Assessment of heavy metal contamination of the technoecosystem of the Kakhovka main canal of the Kakhovka irrigation system - Khokhlova, Liudmyla; Lukashev, Dmytro (Lviv Politechnic Publishing House, 2019)
In the present study, the authors demonstrate the accumulation of heavy metals in water and soft tissues of bivalve mollusks (Dreissena polymorpha, Dreissena bugensis) in the Kakhovka Main Canal within the Kherson and Zaporizhzhia regions (Ukraine) in the summer season (July–August 2018). The average metal concentrations in water decrease in the following order: Ni>Zn>Cr>Co>Cu>Cd. On the whole, the accumulation of metals in soft tissues of the investigated bivalve mollusk species was higher than in the samples of water, since Dreissena are effective bio-accumulators. The average metal concentrations in soft tissues decrease in the following order: Zn>Cr>Ni>Cu>Co>Cd. At the end of the canal, at the 132nd km (Zaporizhzhia region), where older individuals prevailed, heavy metals were accumulated most – 159.04 mg/kg.
Keywords: Dreissena; canal; heavy metals; bioaccumulation; background concentration